2005
DOI: 10.1002/bmb.2005.494033022445
|View full text |Cite
|
Sign up to set email alerts
|

The metabolic effects of low‐carbohydrate diets and incorporation into a biochemistry course

Abstract: One of the challenges in teaching biochemistry is facilitating students' interest in and mastery of metabolism. The many pathways and modes of regulation can be overwhelming for students to learn and difficult for professors to teach in an engaging manner. We have found it useful to take advantage of prevailing interest in popular yet controversial weight-loss methods, particularly low-carbohydrate diets. The metabolic rationale behind these eating plans can be linked to glycolysis, the citric acid cycle, lipo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 60 publications
1
15
0
3
Order By: Relevance
“…In addition, the AHA/NHLBI report [90] presents the rationale for low CHO as the effect on appetite. Whereas this may be a component, it has been stated many times, and is part of basic biochemical education [16,93-96], that the rationale of CHO restriction is the control of metabolism by insulin regulation. The effects described above clearly support this.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the AHA/NHLBI report [90] presents the rationale for low CHO as the effect on appetite. Whereas this may be a component, it has been stated many times, and is part of basic biochemical education [16,93-96], that the rationale of CHO restriction is the control of metabolism by insulin regulation. The effects described above clearly support this.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that there is no singular definition of what constitutes a LCHO diet, although a CHO content comprising <26% of calories (or <130 g CHO) has been suggested as a cut‐off . Variations of the LCHO diet differ in their permitted levels of macronutrients, such as the low‐carbohydrate, high‐fat diet, which emphasises the importance of increasing fat consumption , whereas others increase protein to a greater degree . Absolute intakes (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…These results are in agreement with our findings of decreased G6PDH and aldolase activities and increased citrate synthase activity in LC-control group. Pogozelski, Arpaia, and Priore (2005) suggested that increased proteins at the expense of carbohydrate in diet leads to decreased glycolysis, which is compensated by an increase in fat breakdown to satisfy body needs of energy via formation of ketone bodies from fatty acids. Amino acids formed from protein catabolism together with fatty acids were utilized in gluconeogenesis.…”
Section: Discussionmentioning
confidence: 99%